Trends in immobilization following fracture surgery of the wrist and hand in Sweden: A 16-Year Analysis from 2008 to 2023 - Michael Axenhus; Viktor Schmidt (PLoS ONE, 2025)
Introduction Hand and wrist fractures are common orthopaedic injuries, with varied postoperative management strategies. Cast immobilization, traditionally used to ensure fracture stability, is increasingly debated in favour of early mobilization. However, significant regional differences persist. The aim of this study is to analyse regional, age, and sex differences in post-operative cast immobilization rates for hand and wrist fractures in Sweden between 2008 and 2023. Methods This observational, population-based study utilized data from the Swedish National Patient Register, analysing post-operative cast immobilization rates among individuals aged 15 and older. Trends and disparities were examined over time by region, gender, and age group. Results The study found a significant increase in cast immobilization rates across Sweden, with notable differences based on sex and region. By 2023, immobilization rates for men had increased from 46% to 86%, while rates for women increased from 34% to 69%. Conclusion The findings indicate a nationwide trend towards increased immobilization rates, highlighting gender- and region-based disparities. These differences underscore the need for standardized, evidence-based guidelines to ensure equitable and effective patient care across Sweden.